Toxicity of selected essential oil against red flour beetle (Tribolium castaneum) by using fumigant bioassay / Nur Farahikmah Mahmood and Nur ‘Amira Hamid - Mahmood, Nur Farahikmah; Hamid, Nur ‘Amira (Faculty of Plantation and Agrotechnology, 2018)
In Malaysia, the usage of insecticide to control the infestation pest storage can give the effect to the human health and environment because of a chemical substance contains. Insects that associated with the stored product is the spoilage in term of the quality, appearance and lead to an economic loss. The red flour beetle, Tribolium castaneum holds the significant place in Malaysia by causing damages on stored products. Since the insecticides already resistance to stored product beetles, the main objectives of this research are to determine the effectiveness Citrus sinensis essential oil against red flour beetle T. castaneum. Fumigant toxicity of the EO was tested at different concentration and mortality was recorded every 3, 6, 12 and 24 hours. 10ml of C. sinensis has been recorded can control 100% of T. castaneum. The essential oil that been generated from C. sinensis contains d-limonene which is effective in reducing the amount of red flour beetle in storage or mill. Several compounds including citrus peels oil have found to be bioactive which have strong vapor insecticidal activity. It also has the potential in individual fumigation with a preservative model against C. maculatus. The result of the current study suggested that materials derived from C. sinensis can be used as pulse protectant against pests for small scale of farmers and it provide important tools for the development of an Integrated Pest Management (IPM) program.